What can facilitate cooperation: Fairness, ineaulity aversion, punishment, norms or trust? - Urs Steiner Brandt (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2008)
Almost all economic and public choice models assume that all people are exclusively pursuing their own material self-interests and do not care about social goals per se. Several (laboratory) experiments address the question of the general validity of this assumption. A consistent conclusion emerges that a significant number of people deviate from the assumption of selfish rational behaviour; this conclusion is robust with respect to the design of the experiments. Therefore, public choice comes with a price: the conclusions are based on the stylized stereotype of economic man, an assumption that is not fully satisfied. The purpose of this paper is to show how to incorporate otherregarding preferences into an otherwise traditional utility approach without losing predicting power or compromising the rationality assumption. On the contrary, since other-regarding preferences are based on observed behaviour, the predicting power increases; this is demonstrated at the end of this paper, where it is shown how other-regarding preferences can explain the existence and persistence of a welfare state and why people might act sustainably.
Keywords: 330